miR-325–3p targets GSDMD in macrophages to attenuate lung injury induced by Streptococcus equi subsp. zooepidemicus - Yajuan Li; Li Jiang; Qiuguo Fang; Xiali Yu; Jingyu Yu; Shun Li; Yunfei Huang; Feixiang Huang; Jiedan Liao; Qiang Fu (Veterinary Immunology and Immunopathology, 2026)

Efficient dye decolorization via synergistic degradation and adsorption by MnSiBAl metallic glass - Lansong Yang; Junlei Shi; Chen Yang; Shixin Tan; Peixin Fu; Shun-Xing Liang; Yuanzheng Yang (Journal of Environmental Chemical Engineering, 2026)

Study on the identification, generation mechanism and coloring effect of 5,7-dihydroxycoumarin formed from the autoxidation of EGCG - Zi-Xin Zhao; Zhuo-Shun Dai; Jie-Qiong Wang; Jun-Feng Yin; Liang Zhang; Yong-Quan Xu; Yan-Qing Fu (Food Chemistry, 2026)

Activating valence oscillations in reconstructed high-entropy selenide for self-stabilized seawater oxidation through localized lattice oxygen redox - Hai Li; Xiaoliang Zhang; Yangyang Liu; Taiping Fang; Xue Zou; Gui Wang; Shun Wan; Hongliang Dong; Zihao Lu; Yufan Wu; Jinhui Fu; Luobin Cao; et al. (Science Bulletin, 2026)

Permian A-type felsic magmatism in the South Tianshan Orogenic Belt: Crustal melting triggered by the Tarim mantle plume - Zhi-Hao Song; Xian-Tao Ye; Xiao-Qiang Liu; Hong-Ran Wang; Ming-Can Yang; Shun-Hao Fu; Chuan-Lin Zhang (Lithos, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Symmetry-mismatch-guided topological evolution in pore-space-partitioned metal-organic frameworks for enhanced ethylene purification - Zhang-Lei Zhong; Chen-Chen Xing; Yan-Yu Zhang; Ai-Ming Zhang; Le-Wei Zheng; Yu Wang; Wenyu Yuan; Ying Wang; Shun-Fu Du; Quan-Guo Zhai (Chemical Engineering Journal, 2026)

Effects of personality and body weight on foraging behavior and vigilance: a case study in a small rodent - Yu-Chuang Hui; Shu-Jing Gao; Xuan-Wen Li; Wei-Qi Chen; Yue-Yue Yang; Xue-Dong Bai; Qin Su; Fu-Shun Zhang; Li-Qing Wang; Ling-Ying Shuai (Behavioral Ecology and Sociobiology, 2026)

Characteristics of mud and water inrush disasters in high water pressure filled karst tunnels and the evolution law of surrounding rock response - An Pengtao; Liu Shun; Zhang Wenjun; Fu Helin (Tunnelling and Underground Space Technology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Maridesulfovibrio caeruleilacunae sp. nov. and Maridesulfovibrio oucae sp. nov., two sulfate-reducing bacteria isolated from Yongle Blue Hole of the South China Sea - Wei Dai; Yifan Zhuang; Wen Sun; Tianyu Fu; Chao Jia; Liang Fu; Peng Yao; Zuosheng Yang; Shun Zhou; Xiaochong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2026)

Seasonal temperature rise influences nitrous oxide and methane accumulation in freshwater habitats via distinctive microbial processes - Teng-Fei Ma; Wen-Ke Liu; Chong-Yang Xing; Ya-Song Chen; Hui-Min Fu; Ji-Chun Bai; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Meng-Wen Peng (Environmental Pollution, 2026)

Plant-Based Protein Fermentation Medium Optimization for Antimicrobial Cell-Free Supernatant Production by Lactiplantibacillus plantarum K014 Against Cutibacterium acnes - Yee Ling Kong; Joo Shun Tan; Choon Fu Goh (Probiotics and Antimicrobial Proteins, 2026)

Modulating d-band center to construct Ptδ–Cuδ+ pairs for selective hydrogenation of renewable furfural - Liangmin Ning; Shuai Li; Shiyan Sheng; Jiuheng Ma; Jiawen Wang; Tianyu Zhang; Shun Wang; Jingyi Han; Jiaoyang Wang; Wei Chen; Meng Gao; Kunhua Wang; et al. (Chemical Engineering Journal, 2026)

Complex variable solution for multi-step shallow tunnel excavation considering gravitational effects - Luo-bin Lin; Fu-quan Chen; Chang-jie Zheng; Shang-shun Lin (Tunnelling and Underground Space Technology, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

An electrocatalytic dual molecularly imprinted polymer-based biosensor enables femtomolar detection of CD44 without antibodies - Ping Xia; Cheng Chen; Ruifang Bai; Weige Dong; Yuchun Fu; Chungu Zhang; Lianhai Shan; Shun Feng (Analytica Chimica Acta, 2026)

An interpretable machine learning model for predicting p-y curves of monopiles in clay - Biao Li; Wen-Gang Qi; Yi-Fa Wang; Fu-Ping Gao; Lu Jing; Shun-Yi Wang; Ben He (Ocean Engineering, 2026)

Soil moisture dynamics and rainfall infiltration across vegetation types in subtropical ecosystems in Southwest China - Qiao-Shun Yan; Yu-Xi Peng; Xiao-Jin Jiang; Pei-Li Fu; Zhi-Yun Lu; Xiao-Wen Hu; Yong-Jiang Zhang; Jiao-Lin Zhang; Ze-Xin Fan (CATENA, 2026)

Physics-based unified formulation for predicting clear-water equilibrium scour depth and scour threshold velocity around piles - Wen-Gang Qi; Biao Li; Shun-Yi Wang; Yong Wan; Pei-Qing Zhao; Fu-Ping Gao (Coastal Engineering, 2026)

APOBEC3B-driven mutations negatively regulated by P53 promote tumor progression and immunosuppressive microenvironment in prostate cancer - Yan Guo; Haodi Yu; Xiang Li; Lina Liu; Jing He; Xin Wang; Hui Zhang; Qingyu Zhang; Jing Fu; Ruixue Gu; Hehe Li; Dengfei Xu; et al. (Molecular and Cellular Biochemistry, 2025)

Using UAV multispectral image data to monitor the nitrogen status of head cabbage shoots in the Liupan Mountain area of China - Shuai Wang; Long-Guo Wu; Hua Ma; Kelsang Choron; Fu-Shun Zheng; Zhong-Ting Song; Cui Yin; Hong-Yan Zhu; Peng-Yuan Lv; Yun-e Cao (International Journal of Remote Sensing, 2025)

Numerical calculation of line heating for hull curved plate based on strain direct boundary - Shun Wang; Haohao Jia; Yuxuan Fu; Ji Wang; Rui Li (Ocean Engineering, 2025)

Migration mechanisms of leaking hydrogen sulfide in inter-stratified coal-petroleum basins and mitigation with alkali injection - Shun Liang; Hongye Luo; Derek Elsworth; Qiangling Yao; Xuehai Fu; Qiang Wang; Xuehua Li; Weisheng He; Zhi Ma; Guangli Huang; Furong Wang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Tailoring anchoring functionalities of self-assembled materials for efficient wide-bandgap perovskite solar cells - Zhong-En Shi; Yu-Fan Fu; Bo-Shun Peng; Ting-Chun Hung; Deebakkrishnan Ganesan; Rajendiran Balasaravanan; Shao-Huan Hong; Cheng-Liang Liu; Chun-Jen Su; Ming-Chou Chen; Chih-Ping Chen (Chemical Engineering Journal, 2025)

Low-temperature microwave pyrolysis PVC to achieve modulation of elemental chlorine migration and conversion: performance evaluation of microwave absorption-catalysis-chlorine fixation trifunctional catalyst - Wenjun Fu; Juan Luo; Shichang Shun; Jiangyi Luo; Chengling Liu; Rui Ma (Chemical Engineering Journal, 2025)

Physically exposing tumoral “danger signals” and antigens in vitro - Shun-Yu Wu; Fu-Gen Wu (Science Bulletin, 2025)

Evolution of immunoglobulin M (IgM) structure and function in vertebrates: A comprehensive review - Shun Yang; Lu-Chuan Zhao; Fu-Zhen Guo; Hong-Sen Xu; Meng-Meng Huang; Hui Fei (Fish & Shellfish Immunology, 2025)

Phylogeography of a Small Mammal ( Blarinella quadraticauda ) Distributed Around the Sichuan Basin, Southwest China - Qing Liu; Yu Deng; Rong‐Hui Fan; Chang‐Kun Fu; Xu‐Ming Wang; Shao‐Ying Liu; Shun‐De Chen (Zoologica Scripta, 2025)
The rapid climatic fluctuations and geographical factors during the Quaternary glacial period, particularly in the Pleistocene epoch, play a pivotal role in shaping intraspecific genetic diversity. We conducted an investigation into the genetic structure and speciation mechanisms of a small mammal species, Asiatic Short‐Tailed Shrew ( Blarinella quadraticauda ), which is mainly distributed in the mountains surrounding the Sichuan Basin and its adjacent regions in southwest China. Extensive sampling was conducted across the region (180 Asiatic Short‐Tailed Shrews from 67 sites), followed by principal component analysis and discriminant analysis on complete skull data. Phylogenetic analyses were conducted using mitochondrial (Cytb) and nuclear (APOB and BRCA1) genes. Additionally, the potentially suitable distribution range under both current and historical climatic conditions was projected. Our results show that B. quadraticauda in the Sichuan Basin is divided into six major clades, which are largely morphologically similar, except for the clade from Baoxing, Sichuan, which exhibits a slightly larger size. Additionally, the species exhibits a nearly ring‐like distribution around the Sichuan Basin. Genetic exchange among populations in the northern and eastern regions of the basin appears to be limited, suggesting potential barriers to gene flow. Under the influence of the basin's lowlands, the rapid climate oscillation of the Quaternary glacial period and the uplift of the Tibetan Plateau, the species appears to have formed a ring distribution in the Sichuan Basin. Moreover, we have also updated the taxonomy and distribution range of B. quadraticauda .

Wearable multimodal flexible sensor based on layer-by-layer aerogel/nanofibers composite structure for real-time information encoding and gesture recognition - Zhenshuai Wan; Peng Liu; Yu Fu; Yibin Fan; Shun Peng; Chengqian Zhang; Ye Tian; Shuangkun Wang; Longwang Yue; Ronghan Wei (Chemical Engineering Journal, 2025)

Microemulsion-based formulation of enterocin CC2: a novel antimicrobial solution targeting Streptococcus mutans - Zhang Jin Ng; Choon Fu Goh; Ana Masara Ahmad Mokhtar; Rozi Nuraika Binti Ramli; Chee Keong Lee; Joo Shun Tan (Drug Delivery and Translational Research, 2025)

miR-7002-5p targets caspase-1 to suppress the inflammatory response of macrophages induced by Streptococcus equi subsp. zooepidemicus - Honglin Xie; Jingfei Deng; Jingyu Yu; Shun Li; Yibo Wang; Yajuan Li; Yunfei Huang; Qinqin Sun; Jiedan Liao; Ziteng Deng; Qiang Fu (Archives of Microbiology, 2025)

A low oxygen threshold for physiological responses and trace metal quotas of Prochlorococcus and Synechococcus - Joan De Vera; Yuanyuan Feng; Feixue Fu; Shun‐Chung Yang; Amjad Mansour; Nicholas J. Hawco; David A. Hutchins; Seth G. John (Limnology and Oceanography, 2025)
Continued human activity is expected to accelerate ocean deoxygenation, leading to the expansion and shallowing of oxygen‐deficient zones (ODZs). This decline in oxygen may impact both phytoplankton growth and trace metal uptake. We conducted culture experiments with Prochlorococcus MIT9313 and Synechococcus XM‐24, two numerically dominant genera of marine picocyanobacteria, under varying O 2 levels (36–242 μ M). These experiments provide some of the first data on trace metal quotas in phytoplankton under varying O 2 conditions in culture. Moderate deoxygenation, above hypoxic levels, did not negatively impact the growth and trace metal quotas of either Prochlorococcus MIT9313 or Synechococcus XM‐24 (80 and 85 μ M O 2 , respectively). Indeed, some parameters (e.g., growth rate, carbon fixation and chlorophyll fluorescence) suggest slight growth enhancement at these moderate levels of deoxygenation. However, hypoxic conditions (36 μ M O 2 ) significantly inhibited the growth of Prochlorococcus MIT9313, suggesting a minimum O 2 threshold needed to prevent disruptions in O 2 ‐dependent processes. Synechococcus XM‐24 exhibited no significant response to elevated p CO₂ (1054 μ atm), indicating possible adaptation to variable coastal CO₂ environments. Changes in trace‐metal quotas (metal‐to‐phosphorous ratios; metal/P) were also observed when Prochlorococcus MIT9313 was cultured under hypoxia, including up to 48% increases in Fe/P, 48% decreases in Ni/P, and 27% decreases in Co/P, compared to oxic conditions. These results contrast with elevated metal/P ratios in autotrophic‐associated particles from ODZs, suggesting either distinct metal uptake strategies by phytoplankton in low‐O 2 regions or that elevated particulate metals are influenced by other plankton types such as heterotrophs.

Establishment of an efficient in vitro regeneration protocol for Dendrobium primulinum Lindl. by one-step seedling formation - Cheng-Li Liu; Jie-Mei Deng; Shun Peng; Heng-Yu Huang; Fu-Rong Xu (In Vitro Cellular & Developmental Biology - Plant, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

Synergistic bimolecular erosion-healing interfacial passivation for wide-bandgap perovskite and tandem solar cells - Shiqiang Fu; Guang Li; Shun Zhou; Jiahao Wang; Dexin Pu; Lishuai Huang; Zhiqiu Yu; Wanping Chen; Guojia Fang; Weijun Ke (Science Bulletin, 2025)

The effect of catalyst preparation methods on biomass hydrothermal liquefaction: Exploring cleaner and more efficient pathways for catalytic hydrothermal liquefaction of biomass - Gui-zhong Deng; Xiao-dong Tang; Jing-jing Li; Si-hao Ling; Fu-xiang Yang; Shun-guo Wang (Fuel, 2025)

Fractionation of phosphate oxygen isotope in the leachate of phosphogypsum during its infiltration - Fen Xu; Shun Fu; Haiyan Hu; Jiahao He; Shimeng Mou; Yanhua Xie (Journal of Environmental Management, 2025)

Characterizing Holocene environmental transitions using magnetic properties of sediments from the continental shelf of the northern South China Sea - Yi Wu; Guanqiang Cai; Shun Li; Shixun Wang; Shuqing Fu; Yulin Han; Shichen Tao (Marine Geology, 2025)

Mechanical properties and analytical solutions of ring linings in prestressed hydraulic tunnel - Yanbin Fu; Shun Wang; Liping Huang; Andian Lu; Yanlong Zhang; Xiaolong Zhang; Guangliang Yao; Yue Gao (Tunnelling and Underground Space Technology, 2025)

Effect of wall slip of CO2-in-water foams on enhanced oil recovery - Biao Xu; Jiuqing Li; Lin Zhu; Junyan Xu; Runze Wang; Shun Li; Jiajia Fu; Jingyi Yang; Tao Liu (Chemical Engineering Journal, 2025)

Evaluating long-term reductions in trace metal emissions from shipping in Shanghai - Meng Wang; Yusen Duan; Juntao Huo; Jia Chen; Yanfen Lin; Qingyan Fu; Tao Wang; Yu Huang; Junji Cao; Shun-cheng Lee (Journal of Hazardous Materials, 2024)

Sustainability-inspired upcycling of plastic waste into porous carbon nanobulks for water decontamination via peroxymonosulfate activation - Kun Pang; Fangyu Fu; Haoqi Wang; Shun Ding; Yanfen Fang; Xiang Liu (Science of The Total Environment, 2024)

A point-of-care testing strip based on a rationally designed antigen and antibody for fast and reliable Diquat poisoning detection: Ready for clinical application - Shun Zhang; Guanyan Fu; Weijing Yi; Jiahui Zhou; Wenbin Liang; Wanjiang Zhao; Tian Zhang; Gen Zhang; Jing Zhang; Huiling Li; Huifang Yan; Banghua Wu; et al. (Chemical Engineering Journal, 2024)

A thermoresponsive metabolic nanomodulator for achieving photochemotherapy-sensitized cancer immunotherapy - Shun-Yu Wu; Xiao-Yu Zhu; Xinping Zhang; Yong-Xi Zhou; Shao-Zhe Wang; Yan-Hong Li; Shi-Jie Hao; Tian-Yu Wang; Xin-Wang Yu; Yuxin Guo; Guang-Yu Pan; Bin Xu; et al. (Chemical Engineering Journal, 2024)

Prediction of surface urban heat island based on predicted consequences of urban sprawl using deep learning: A way forward for a sustainable environment - Shun Fu; Lufeng Wang; Umer Khalil; Ali Hassan Cheema; Israr Ullah; Bilal Aslam; Aqil Tariq; Muhammad Aslam; Saad S. Alarifi (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Scour-induced unloading effects on lateral response of large–diameter monopiles in dense sand - Li Biao; Qi Wen-Gang; Wang Yifa; Gao Fu-Ping; Wang Shun-Yi (Computers and Geotechnics, 2024)

Proton transfer induced persistent triplet charge transfer phosphorescence in molecule-doped polymer systems - Shulin Liu; Chensheng Li; Liyun Liao; Yanping Huo; Zhong-Min Su; Fu-Shun Liang; Yingxiao Mu (Chemical Engineering Journal, 2024)

Extrapolating time development curves of clear-water scour around piles: From empirical fitting to physics-based approach - Shun-Yi Wang; Wen-Gang Qi; Biao Li; Zhan Wang; Fu-Ping Gao (Ocean Engineering, 2024)

A new species of Eirictis (Mammalia, Carnivora, Mustelidae) from Lower Pleistocene of Yuanmou Basin, Yunnan, China - Arya Farjand; Li-Ya Fu; Qi-Gao Jiangzuo; Zhi-Heng Liu; Jian Wang; Xin-Ying Zhou; Shun-Dong Bi; Li-Hua Wang (Palaeoworld, 2024)

Tidal currents-induced scour development around pile foundations: Effects of flow velocity hydrograph - Shun-Yi Wang; Wen-Gang Qi; Biao Li; Chen Wang; Fu-Ping Gao (Coastal Engineering, 2024)

Enteral nutrition in the management of acute pancreatitis: Modulates gut microbiome and alleviates inflammation - Fang-Yuan Yang; Yi-Jing Cai; Xiao-Ying Niu; Shun-Fu Wang; Yu-Qi Wang; Sabola Eluby Esmie; Rui-Cong Chen; Sheng-Jie Dai; Hong-Ru Kong; Hong-Wei Sun; Ke-Qing Shi (Food Bioscience, 2024)

A one-step polyphenol-based functionalization strategy of dual-enhanced antibacterial and osteogenic surfaces - Xiao Chen; Meizhou Sun; Lujiao Zhang; Yang Hu; Zhiwei Yang; Shun Duan; Fu-Jian Xu; Juehua Jing (Chemical Engineering Journal, 2024)

Time development of clear-water scour around a pile foundation: Phenomenological theory of turbulence-based approach - Shun-Yi Wang; Wen-Gang Qi; Fu-Ping Gao; Biao Li; Ben He (Coastal Engineering, 2024)

The impact of elevated CO2 concentration on photosynthesis, growth and hydraulics of evergreen and deciduous tree seedlings from a subtropical forest in Southwest China - Pei-Li Fu; Ya Zhang; Jin-Hua Qi; Yong-Jiang Zhang; Guang-You Hao; Patrick M. Finnegan; Qiao-Shun Yan; Ze-Xin Fan (Agricultural and Forest Meteorology, 2024)

Causes of episodic movement of the Baijiabao landslide based on multiple-time scale analysis - Zhiyong Fu; Dian-Qing Li; Shun Wang; Limin Zhang; Wenqi Du (Landslides, 2024)

Nanosized lanthanum peroxide–loaded biochar composites for simple and effective glyphosate removal from wastewater: Behavior and mechanisms - Xuewen Xie; Yanhua Xie; Kaixia Zuo; Jie Wu; Shun Fu; Weiwei Li; Philip M. Haygarth (Journal of Cleaner Production, 2024)

Analytical solution to the mechanical response of grouting lifting in existing shield tunnels and engineering case verification - Yanbin Fu; Shun Wang; Ze Wu; Xuezhong Zhang; Junzhou Zhu; Beiling Wang; Yelei Huang (Tunnelling and Underground Space Technology, 2024)

CRISPR/Cas9-mediated ebony knockout causes melanin pigmentation and prevents moth Eclosion in Ectropis grisescens - Jia-Li Li; Shun-Si Li; Zi-Jun Luo; Ji Lu; Xiao-Ming Cai; Zong-Xiu Luo; Lei Bian; Chun-Li Xiu; Nan-Xia Fu; Nai-Yong Liu; Zhao-Qun Li (Pesticide Biochemistry and Physiology, 2024)

Simplification of the pretreatment method for phosphate oxygen isotope measurement in phosphogypsum leachate - Yanhua Xie; Zifan Wu; Xuewen Xie; Shun Fu; Shujie Liu; Shimeng Mou; Xiangjun Pei (Journal of Environmental Management, 2024)

A new complex variable solution on noncircular shallow tunnelling with reasonable far-field displacement - Luo-bin Lin; Fu-quan Chen; Shang-shun Lin (Computers and Geotechnics, 2024)

A metal-phenolic network-assembled nanotrigger evokes lethal ferroptosis via self-supply loop-based cytotoxic reactions - Xinping Zhang; Yuxin Guo; Xiaoyang Liu; Shun-Yu Wu; Ya-Xuan Zhu; Shao-Zhe Wang; Qiu-Yi Duan; Ke-Fei Xu; Zi-Heng Li; Xiao-Yu Zhu; Guang-Yu Pan; Fu-Gen Wu (Chemical Engineering Journal, 2024)

Targeted regulation of the microbiome by green manuring to promote tobacco growth - Hai Liang; Shun Li; Guopeng Zhou; Libo Fu; Feng Hu; Songjuan Gao; Weidong Cao (Biology and Fertility of Soils, 2024)

Molecularly imprinted electrochemical sensor based on metal-covalent organic framework for specifically recognizing norfloxacin from unpretreated milk - Yuchun Fu; Yang Xie; Haizhu Shi; Guowei Zhang; Huaju Zhang; Shun Feng (Food Chemistry, 2023)

Permeability evolution and production characteristics of inclined coalbed methane reservoirs on the southern margin of the Junggar Basin, Xinjiang, China - Shun Liang; Yaowu Liang; Derek Elsworth; Qiangling Yao; Xuehai Fu; Junqiang Kang; Yisong Hao; Meng Wang (International Journal of Rock Mechanics and Mining Sciences, 2023)

Telomere length, oxidative stress and their links with growth and survival in a lizard facing climate warming - Qiong Zhang; Xing-Zhi Han; Pablo Burraco; Xin Hao; Li-Wei Teng; Zhen-Sheng Liu; Fu-Shun Zhang; Wei-Guo Du (Science of The Total Environment, 2023)

Combined effects of light pollution and vegetation height on behavior and body weight in a nocturnal rodent - Ling-Ying Shuai; Li-Qing Wang; Yang Xia; Jin-Yu Xia; Kang Hong; Ya-Nan Wu; Xin-Yi Tian; Fu-Shun Zhang (Environmental Pollution, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Porewater dissolved inorganic carbon released due to artificial sediment scouring in the Yellow River - Xing-yu Huang; Dong Zhang; Fu-shun Wang; Zhi-qi Zhao; Ai-chun Chen; Jun-wen Zhang; Cong Zhang; Li Wu; Yu-hong Li; Bing-juan Ma; Qi-yan Feng (Applied Geochemistry, 2023)

Unique bacterial communities and lifestyles in deep ocean blue holes: Insights from the Yongle Blue Hole (South China Sea) - Shun Zhou; Jiwen Liu; Peng Yao; Liang Fu; Zuosheng Yang; Yulin Zhang; Rui Du; Chao Jia; Lin Chen; Jinchang Liang; Xiaolei Wang; Xiaochong Shi; et al. (Frontiers in Marine Science, 2023)
Deep ocean blue holes possess steep physicochemical gradients, especially low dissolved oxygen concentration, which shape the extraordinary microbial communities. However, the environmental responses of microorganisms with different lifestyles and knowledge of culturable microorganisms in the blue holes are still unknown. Here, we investigated the bacterial community structure with different lifestyles of the world’s deepest blue hole - the Yongle Blue Hole (YBH) in the South China Sea using both culture-dependent and -independent methods. YBH can be divided by oxygen content into an oxic zone, a suboxic zone and two anoxic zones. The abundance of bacteria, archaea, genes dsrB and soxB were all higher in the free-living (FL) lifestyle than in the particle-associated (PA) lifestyle, yet the diversity and richness of PA bacteria were higher than that of FL bacteria. More Gammaproteobacteria and less Alphaproteobacteria , Chloroflexi and Nitrospinae were observed within the FL fraction than within the PA fraction. The relative abundance of sulfur-oxidizing bacteria (SOB) was dominant between 100-140 m (anoxic zone I) in YBH, with a maximum of 90.0% (140 m FL fraction). The SOB in YBH were mainly colorless sulfur bacteria and purple non-sulfur bacteria, of which Thiomicrorhabdus and Sulfurimonas were the main representatives. In addition, a total of 294 bacterial strains were isolated on a variety of media and culture conditions, and 22.2% (18/81) of anaerobic strains were identified as potential novel species. Our study reveals a distinction between FL and PA bacteria in YBH. It contributes to further understanding of the bacterial community in deep ocean blue holes, and provides bacterial resources for subsequent studies on their adaptation to extreme marine environments.

Selective luminescent sensing of teflubenzuron and oxyfluorfen by a resorcin[4]arene-based metal-organic framework - Bing-Bing Lu; Zhi-Xin Xing; Yong-Shun Bao; Fei Ye; Ying Fu (Chemical Engineering Journal, 2023)

Scalable anti-infection polyurethane catheters with long-acting and autoclavable properties - Zongpeng Xiu; Meiping Yang; Ruonan Wu; Chengyue Lei; Hui-Min Ren; Bingran Yu; Shuai Gao; Shun Duan; Dimeng Wu; Fu-Jian Xu (Chemical Engineering Journal, 2023)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

Diel variation in anti-predation behavior of a ground squirrel and relationships between vigilance and escape - Ling-Ying Shuai; Mei-Ting Liu; A.-Ping Zhu; Yuan-Yuan Cao; Fu-Shun Zhang (Behavioral Ecology and Sociobiology, 2022)

Characterization of Coal Structure of High-Thickness Coal Reservoir Using Geophysical Logging: A Case Study in Southern Junggar Basin, Xinjiang, Northwest China - Junqiang Kang; Xuehai Fu; Jian Shen; Shun Liang; Hao Chen; Fuhua Shang (Natural Resources Research, 2022)

Research and application of a comprehensive forecasting system for tunnels in water-bearing fault fracture zones: a case study - Chang-fu Huang; Shuai-long Zhang; Shun-chuan Wu; Yong-tao Gao (Arabian Journal of Geosciences, 2022)

Two new troponoides with anti-inflammatory activity from the stems of Juniperus formosana Hayata - Dong Zheng; Jian-Yu Zhang; Wen-Hao Fu; Shun-Zhi Liu; Su-Zhi Xie; Zheng Wang; Ying-Kun Qiu (Natural Product Research, 2021)

A reciprocal egg-swap experiment reveals sources of variation in developmental success among populations of a desert lizard - Xin Hao; Chen-Xu Wang; Xing-Zhi Han; Yang Wang; Qiong Zhang; Fu-Shun Zhang; Bao-Jun Sun; Wei-Guo Du (Oecologia, 2021)

SNX-2112, an Hsp90 inhibitor, suppresses cervical cancer cells proliferation, migration, and invasion by inhibiting the Akt/mTOR signaling pathway - Liang-Shun Fu; Hong-Hong Qiu; Min Liu; Liu-Bing Hu; Yan Wang; Peng-Chao Zhang; Man-Mei Li; Yi-Fei Wang; Zhong Liu (Medicinal Chemistry Research, 2020)

Multi-hole joint acquisition of a 3D-RVSP in a karst area: Case study in the Wulunshan Coal Field, China - Ming-Shun Hu; Dong-Ming Pan; Fu-Bao Zhou; Juan-Juan Li; Yang-Zhou Wang; Shen-En Chen; Yong-Zhong Xu (Applied Geophysics, 2020)

Vertical variation in Vibrio community composition in Sansha Yongle Blue Hole and its ability to degrade macromolecules - Bei Li; Jiwen Liu; Shun Zhou; Liang Fu; Peng Yao; Lin Chen; Zuosheng Yang; Xiaolei Wang; Xiao-Hua Zhang (Marine Life Science & Technology, 2020)
With the advantages of wide distribution, fast growth, and broad metabolic spectrum to organic carbon compounds, Vibrio may play an important role in organic carbon cycling. However, the ecological roles of Vibrio in many marine environments have not been explored. Here, the world’s deepest ‘blue hole’, the Sansha Yongle Blue Hole (SYBH) in the South China Sea, which is a geographically semi-enclosed environment featuring unique chemical characters, was investigated. The abundance, diversity and carbon source utilization capability of Vibrio were studied by quantification and high-throughput sequencing of Vibrio specific 16S rRNA genes and cultivation methods. The abundance of Vibrio in water column of the SYBH ranged from 3.78 × 10 4 to 7.35 × 10 6 16S rRNA gene copies L −1 . Free-living Vibrio was more abundant than particle-associated Vibrio (~ 1.20 × 10 6 versus~ 2.68 × 10 5 gene copies L −1 ), indicating that Vibrio prefers a free-living life style. The Vibrio assemblages showed clear vertical stratification and could be divided into three groups: aerobic-transition, middle anaerobic and bottom anaerobic zones. Dissolved oxygen (DO), temperature, pH and salinity were the main environmental factors affecting the abundance and community composition. Cultivated Vibrio demonstrated a degrading capability to various macromolecular substrates, including starch, Tween 20/40/80, DNA, gelatin, alginate, casein, chitin, lecithin, κ-carrageenan, mannan, xylan and hyaluronic acid. This suggests that Vibrio could produce a variety of highly active extracellular enzymes. Our study provides new insights into the distribution pattern and possible role in carbon cycle of Vibrio in the unique environment of a ‘blue hole’.

Correction to: Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2019)

Assessment of empirical equations of the compression index of muddy clay: sensitivity to geographic locality - Chang–fu Huang; Qun Li; Shun–chuan Wu; Yang Liu; Jian–yu Li (Arabian Journal of Geosciences, 2019)

Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2018)

Shifts in the structure and function of the microbial community in response to metal pollution of fresh water sediments in Finland - Xue-Ping Chen; Hao-Yu Chen; Jing Sun; Xu Zhang; Chi-Quan He; Xiao-Yan Liu; Xin Huang; Min Yang; Fu-Shun Wang; Kristiina Väänänen (Journal of Soils and Sediments, 2018)

Functional Role of Matrix gla Protein in Glioma Cell Migration - Mu-Hui Fu; Chih-Yen Wang; Yun-Ti Hsieh; Kuan-Min Fang; Shun-Fen Tzeng (Molecular Neurobiology, 2018)

The epigenetic modifications and the anterior to posterior characterization of meiotic entry during mouse oogenesis - Xia-Fei Fu; Fan Yang; Shun-Feng Cheng; Yan-Ni Feng; Lan Li; Paul W. Dyce; Wei Shen; Xiao-Feng Sun (Histochemistry and Cell Biology, 2017)

Cancer risk from gaseous carbonyl compounds in indoor environment generated from household coal combustion in Xuanwei, China - Ka-Hei Lui; Wen-Ting Dai; Chi-Sing Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Bei Wang; Jinwen Li; Jun-Ji Cao; Shun-Cheng Lee; Kin-Fai Ho (Environmental Science and Pollution Research, 2017)

Both AtrbohD and AtrbohF are essential for mediating responses to oxygen deficiency in Arabidopsis - Bo Liu; Lirong Sun; Liya Ma; Fu-Shun Hao (Plant Cell Reports, 2017)

Association of oral endothelin receptor antagonists with risks of cardiovascular events and mortality: meta-analysis of randomized controlled trials - Yu Pan; Chun Hu; Pei Hua Chen; Yan Hong Gu; Qing Yan Qiao; Li Hua Pan; Dong Chi Zhou; Hui Fang Gu; Shun Kun Fu; Hui Min Jin (European Journal of Clinical Pharmacology, 2017)

Permeability of novel 4′-N-substituted (aminomethyl) benzoate-7-substituted nicotinic acid ester derivatives of scutellarein in Caco-2 cells and in an in vitro model of the blood-brain barrier - Yu Ou; Min Luo; Yong-Xi Dong; Hang Su; Xiao-Zhong Fu; Yu-Feng Cha; Shun Zhang; Yong-Long Zhao; Yong-Jun Li; Yong-Lin Wang (Medicinal Chemistry Research, 2016)

l-Amino acid carbamate prodrugs of scutellarin: synthesis, physiochemical property, Caco-2 cell permeability, and in vitro anti-oxidative activity - Yu-Feng Cha; Shun Zhang; Hang Su; Yu Ou; Xiao-Zhong Fu; Feng-Jie Jiang; Yong-Long Zhao; Yong-Xi Dong; Min Luo; Yong Huang; Yan-Yu Lan; Ai-Min Wang; et al. (Medicinal Chemistry Research, 2015)

AtrbohD and AtrbohF negatively regulate lateral root development by changing the localized accumulation of superoxide in primary roots of Arabidopsis - Ning Li; Lirong Sun; Liyue Zhang; Yalin Song; Panpan Hu; Cui Li; Fu Shun Hao (Planta, 2015)

Early-life sleep deprivation persistently depresses melatonin production and bio-energetics of the pineal gland: potential implications for the development of metabolic deficiency - Li-You Chen; Cheng Tiong; Chung-Hung Tsai; Wen-Chieh Liao; Shun-Fa Yang; Su-Chung Youn; Fu-Der Mai; Hung-Ming Chang (Brain Structure and Function, 2015)

Characterization of OsDREB6 responsive to osmotic and cold stresses in rice - Ya-Guang Ke; Zhi-Jun Yang; Shun-Wu Yu; Tian-Fei Li; Jin-Hong Wu; Huan Gao; Ya-Ping Fu; Li-Jun Luo (Journal of Plant Biology, 2014)

Emodin elicits cytotoxicity in human lung adenocarcinoma A549 cells through inducing apoptosis - Wing-Yan Li; Yam-Fung Ng; Huan Zhang; Zi-Dong Guo; De-Jian Guo; Yiu-Wa Kwan; George Pak-Heng Leung; Simon Ming-Yuen Lee; Peter Hoi-Fu Yu; Shun-Wan Chan (Inflammopharmacology, 2014)

Primordial follicle assembly was regulated by notch signaling pathway in the mice - Chun-Lei Chen; Xia-Fei Fu; Lin-Qing Wang; Jun-Jie Wang; Hua-Gang Ma; Shun-Feng Cheng; Zhu-Mei Hou; Jin-Mei Ma; Guo-Bo Quan; Wei Shen; Lan Li (Molecular Biology Reports, 2014)

Sedimentary filling and sequence structure dominated by T-R cycles of the Nenjiang Formation in the Songliao Basin - ChenChen Zhang; Shun Zhang; Wei Wei; ChaoDong Wu; JiangPing Liang; Wen Niu; JinXia Du; XiuLi Fu; KunNing Cui; Chao Wang; Hui Wang (Science China Earth Sciences, 2014)

Differential expression of VGLUT1 or VGLUT2 in the trigeminothalamic or trigeminocerebellar projection neurons in the rat - Shun-Nan Ge; Zhi-Hong Li; Jun Tang; Yunfei Ma; Hiroyuki Hioki; Ting Zhang; Ya-Cheng Lu; Fu-Xing Zhang; Noboru Mizuno; Takeshi Kaneko; Ying-Ying Liu; Mandy Siu Yu Lung; et al. (Brain Structure and Function, 2014)

Influence of Electromagnetic Signal of Antibiotics Excited by Low-Frequency Pulsed Electromagnetic Fields on Growth of Escherichia coli - Yin-Lung Ke; Fu-Yu Chang; Ming-Kun Chen; Shun-Lai Li; Ling-Sheng Jang (Cell Biochemistry and Biophysics, 2013)

Promoting role of an endophyte on the growth and contents of kinsenosides and flavonoids of Anoectochilus formosanus Hayata, a rare and threatened medicinal Orchidaceae plant - Fu-sheng Zhang; Ya-li Lv; Yue Zhao; Shun-xing Guo (Journal of Zhejiang University-SCIENCE B, 2013)

Construction of an integrated genetic map based on maternal and paternal lineages of tea (Camellia sinensis) - Chih-Yi Hu; Tair-Chyang Lee; Hsien-Tsung Tsai; You-Zen Tsai; Shun-Fu Lin (Euphytica, 2013)

Pedobacter hainanensis sp. nov., Isolated from Seaside Soil - Yan-yu Meng; Yun-bin Fu; Meng-yu Wang; Yong Zhao; Qi-shun Liu; Yu-guang Du (Current Microbiology, 2013)

Evaluation and QTL mapping of phosphorus concentration in soybean seed - Keith E. King; Nick Lauter; Shun Fu Lin; M. Paul Scott; Randy C. Shoemaker (Euphytica, 2013)

A review of the anticancer and immunomodulatory effects of Lycium barbarum fruit - Wai-Man Tang; Enoch Chan; Ching-Yee Kwok; Yee-Ki Lee; Jian-Hong Wu; Chun-Wai Wan; Robbie Yat-Kan Chan; Peter Hoi-Fu Yu; Shun-Wan Chan (Inflammopharmacology, 2012)

Development of RT-LAMP and real-time RT-PCR assays for the rapid detection of the new duck Tembusu-like BYD virus - Tao Jiang; Juan Liu; Yong-Qiang Deng; Jing-Liang Su; Li-Juan Xu; Zhi-Hui Liu; Xiao-Feng Li; Xue-Dong Yu; Shun-Ya Zhu; George Fu Gao; E-De Qin; Cheng-Feng Qin (Archives of Virology, 2012)

Structural insights into a human anti-IFN antibody exerting therapeutic potential for systemic lupus erythematosus - Songying Ouyang; Bin Gong; Jin-Zhi Li; Li-Xia Zhao; Wei Wu; Fu-Shun Zhang; Lina Sun; Shu-Jun Wang; Meng Pan; Chuan Li; Wenguang Liang; Neil Shaw; et al. (Journal of Molecular Medicine, 2012)

A review of the pharmacological effects of Arctium lappa (burdock) - Yuk-Shing Chan; Long-Ni Cheng; Jian-Hong Wu; Enoch Chan; Yiu-Wa Kwan; Simon Ming-Yuen Lee; George Pak-Heng Leung; Peter Hoi-Fu Yu; Shun-Wan Chan (Inflammopharmacology, 2011)

Gastric duplication cyst lined by pseudostratified columnar ciliated epithelium: a case report and literature review - Wu Jiang; Bo Zhang; Yan-biao Fu; Jia-wei Wang; Shun-liang Gao; Su-zhan Zhang; Yu-lian Wu (Journal of Zhejiang University-SCIENCE B, 2011)

Molecular cloning and characterization of hatching enzyme-like gene in the silkworm, Bombyx mori - Fu-hao Lu; Shun-ming Tang; Xing-jia Shen; Na Wang; Qiao-ling Zhao; Guo-zheng Zhang; Xi-jie Guo (Molecular Biology Reports, 2010)

Pancreatic somatostatinoma with obscure inhibitory syndrome and mixed pathological pattern - Bo Zhang; Qiu-ping Xie; Shun-liang Gao; Yan-biao Fu; Yu-lian Wu (Journal of Zhejiang University-SCIENCE B, 2010)

Expression of the Vicia faba VfPIP1 gene in Arabidopsis thaliana plants improves their drought resistance - Xiang-Huan Cui; Fu-Shun Hao; Hui Chen; Jia Chen; Xue-Chen Wang (Journal of Plant Research, 2008)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Effect of α-synuclein on the promoter activity of tyrosine hydroxylase gene - Nan Gao; Yao-Hua Li; Xin Li; Shun Yu; Gui-Lian Fu; Biao Chen (Neuroscience Bulletin, 2007)

Importin KPNA2, NBS1, DNA Repair and Tumorigenesis - Shu-Chun Teng; Kou-Juey Wu; Shun-Fu Tseng; Chui-Wei Wong; Li Kao (Journal of Molecular Histology, 2006)

High-level expression of Trigonopsis variabilis D-amino acid oxidase in Escherichia coli using lactose as inducer - Tzann-Shun Hwang; Hui-Mei Fu; Long-Liu Lin; Wen-Hwei Hsu (Biotechnology Letters, 2000)

Background exposure of urban populations to lead and cadmium: comparison between China and Japan - Y.-Q. Wu; Zuo-Wen Zhang; Chan-Seok Moon; Shinichro Shimbo; Takao Watanabe; Feng-Sheng He; Shun-Fu Zhou; Jiang-Bin Qu; M. Ikeda; De-Ming Su (International Archives of Occupational and Environmental Health, 1997)